Nonlinear Adaptive Control for Wind Turbine Under Wind Speed Variation - Abdelhaq.Amar bensaber; Mustapha Benghanem; Mohammed.Amar bensaber; Abdelmadjid. Guerouad (IAES International Journal of Robotics and Automation (IJRA), 2018)
Wind turbines components work as nonlinear systems where electromechanical parameters change frequently [1], which makes nonlinear control an interesting solution to prevail good efficiency. SMC has been largely used in electrical power applications because it offers interesting features like robustness to parametric uncertainties and external disturbances, to conquer the biggest drawback of the SMC, adaptation strategy consists on updating the sliding gain and the turbine torque to contribute with some important characteristics such as chatter-free performance, heftiness, robustness and secure power system operation. Matlab tests are introduced and compared.